Scheduling with Communication Delays via LP Hierarchies and Clustering - Davies, Sami; Kulkarni, Janardhan (Jana); Rothvoss, Thomas; Tarnawski, Jakub; Zhang, Yihao (FOCS 2020, 2020)
We consider the classic problem of scheduling jobs with precedence constraints on identical machines to minimize makespan, in the presence of communication delays. In this setting, denoted by P | prec, c | Cmax, if two dependent jobs are scheduled on different machines, then at least c units of time must pass between their executions. Despite its relevance to many applications, this model remains one of the most poorly understood in scheduling theory. Even for a special case where an unlimited number of machines is available, the best known approximation ratio is 2/3 ·(c + 1), whereas Graham’s greedy list scheduling algorithm already gives a (c + 1)- approximation in that setting. An outstanding open problem in the top-10 list by Schuurman and Woeginger and its recent update by Bansal asks whether there exists a constant-factor approximation algorithm. In this work we give a polynomial-time O(log c · log m)-approximation algorithm for this problem, where m is the number of machines and c is the communication delay. Our approach is based on a Sherali-Adams lift of a linear programming relaxation and a randomized clustering of the semimetric space induced by this lift.